Developing a CO2 Emission Trading Scheme for Malaysian Cement Industry (S/O: 13251) - Bakhtyar, Bardia; Ibrahim, Yusnidah; Ahmad, Siti Aznor; Islam, Rabiul
The Cement production sector consumes significant amount of energy depending upon the process and technology being used. The approximate consumption of energy by cement industry is around 12-15 percent energy of total energy produced. Therefore, it is necessary to identify wastage of energy so that essential actions could be taken to decrease energy wastage in cement sector. The researchers intend to present the different sources of energy that is being consumed at various sections in Malaysian cement industry and the measures that could be applied for energy savings. In the current study manufacturing processes of cement industry is also described. The production phase and capacity of cement plants that are operating in Malaysia are also discussed in the study. It has been concluded that fuel is a major part of energy that uses in cement industry but now the industry move towards other sources of energy. The electricity consumption of modem cement plant is 110---120 kWh for the manufacturing of one tone cement. It also has been reported that cement industry shifting to dry process that use less energy as compare to wet process. During the process of manufacturing huge amount of emissions are also released which result in atmosphere damage. For these reasons special attention is required on the clinker production to reduce CO2 emission, for this there are various effective measures can be taken into account. Capturing CO2 and store it away into the soil or ocean can be very helpful for reduction in emission up to 65-70% as researcher found. However, it is identified that alternative source of energy will be helpful to reduce the emission of Carbon dioxide. These measures will reduce the negative impact over the climate and atmosphere as well as quality production of cement products